Social influences as correlates of unsafe Internet behaviour among in-school adolescents in Nigeria (2016)
Social networks have become progressively more popular as a way for people to communicate and accessing the internet has also been made very easy through hand held and other devices. Unfortunately, many adolescents are left on the internet and granted unlimited access without monitoring which is necessary to ensure their online safety. A trend that could expose them to unhealthy and addictive behaviour with resultant effect on their academics, social and mental health. Regulating unsafe internet behaviour is an important issue for research. This study was designed with the aim of understanding social influences which correlates with unsafe internet behaviour among in-school adolescents in Ibadan North Local Government area of Oyo State, this is important to provide empirical data baseline to drive internet safety interventions. Descriptive research design was employed and a sample of 1154 was selected using a multi stage sampling technique. A self-developed and validated questionnaire titled Unsafe Internet Behaviour and Social Correlates Questionnaire with reliability index of 0.84 on the Cronbach alpha scale was used to generate data which were analysed using Pearson Product Moment Correlation Coefficient at 0.05 alpha level. The findings of the study showed that family influence(r=0.519, df=1153, p=0.000<0.05), peer influenced=0.411, df-1153, p=0.000<0.05), school influence(r=0.557, df=1153, p=0.000<0.05), and media influence(r=0.606, df=1153, p=0.000<0.05) all significantly correlated with unsafe internet behaviour. Parental involvement and supervision should be a foundational component of internet safety education.